Research and Application of Grid-Connected Control Strategy for Grid-Forming Photovoltaic Inverters - YIN Haibo; ZHU Qiliang (Kongzhi Yu Xinxi Jishu)
With the widespread integration of power electronic converters in power grids, particularly in new energy fields such as photovoltaic power (PV), wind power, and energy storage, power systems have encountered continuous inertia declines, accompanied by the prevalence of weak grid environments, leading to frequent grid failures. To solve these challenges, this paper proposes a grid-connected control strategy designed for grid-forming photovoltaic inverters based on synchronous generators (SG). The strategy includes an active frequency control loop and a reactive voltage control loop derived from the rotor mechanical equation and stator electrical equation for SGs. The active frequency control loop is used to simulate the primary frequency regulation function of synchronous motors, while the reactive voltage control loop to imitate the reactive voltage regulation process of synchronous motors, thereby enabling the photovoltaic inverters to actively support grids and adjust system inertia in weak grid environments or in case of grid failures. Moreover, these voltage and current control loops are utilized to accurately control the output voltage and current from the inverters, achieving closed-loop control on them. To verify the regulation and support capabilities of the proposed control strategy for power grids, simulation experiments and hardware-in-loop experiments were conducted based on a hardware-in-loop simulation platform and controller hardware chassis. Through experiments such as primary frequency regulation and fault ride-through, the inverters' capabilities in adjusting output active and reactive power in response to grid faults were verified. With demonstrated efficacy in providing active, reactive, and inertia support for grids, the proposed inverter design ensures continuous operation without grid disconnection in case of changes in grid frequency and voltage.